Successful treatment of a bowel fistula in the open abdomen by perforator flaps and an aponeurosis plug - Sashida, Yasunori; Kayo, Munefumi; Hachiman, Hironobu; Hori, Kazuki; Kanda, Yukihiro; Nagoya, Akihiro (Archives of Plastic Surgery, 2018)
In this report, we present a case of successful treatment of a bowel fistula in the open abdomen by perforator flaps and an aponeurosis plug. A 70-year-old man underwent total gastrectomy and developed anastomotic leakage and dehiscence of the abdominal wound a week later. He was dependent upon extracorporeal membrane oxygenation, continuous hemodiafiltration, and a respirator. Bowel fluids contaminated the open abdomen. Two months after the gastric operation, a plastic surgery team, in consultation with general surgeons, performed perforator flaps on both sides and constructed, as it were, a bridge of skin sealing the orifice of the fistula. The aponeurosis of the external oblique muscle was elevated with the flap to be used as a plug. The perforators of the flaps were identified on preoperative and intraoperative ultrasonography. This modality allowed us to locate the perforators precisely and to evaluate the perforators by assessing their diameters and performing a waveform analysis. The contamination decreased dramatically afterwards. The bare areas were gradually covered by skin grafts. The fistula was closed completely 18 days after the perforator flap. An ultrasoundguided perforator flap with an aponeurosis plug can be an option for patients suffering from an open abdomen with a bowel fistula.
Keywords: Intestinal fistula; Perforator flap; Ultrasonography, Doppler; Abdominal wound closure techniques